Shifting Roles in Gender, Kinship, and the Household: Women's Empowerment in Matrilineal Malawi - Kuzara, Jennifer L (ProQuest Dissertations & Theses, 2014)
Gender roles, including by definition women's rights in relation to family and home, have been a fundamental subject of anthropological inquiry from the birth of the discipline. The efforts of social anthropologists of the early- and-mid twentieth-century to study and catalogue kinship systems resulted in elaborate detail across numerous cultures on questions of how natal and marital kin formally and informally negotiate rights to children, property, and self-determination, and enabled cross-cultural comparison of facets of household life; in other words, definitional correlates of women's empowerment. The present study examines this question empirically in contemporary Malawi. First, the study explores theories of whether matrilineality is empowering for women. It then contextualizes Chewa matrilineality against a period of rapid historical and demographic change, seeking to reconstruct Chewa gender norms over time. The primary analysis assesses women's relative empowerment across critical individual, relational, and social domains, and compares correlates of empowerment in women in two districts in Malawi, one historically and ethnographically matrilineal (demographically majority Chewa), and one historically and ethnographically patrilineal (demographically majority Ngoni), including a direct measure of whether women reported living in a household that was matrilineal or patrilineal, the composition of their households, and characteristics that map onto historical features of Chewa matrilineality, such as ownership of land and other assets, female household headship, and whether husbands reside with them. Matrilineage membership among contemporary Malawians was not found to be associated with the features that were once described as part of Chewa life; neither did it associate with ethnicity or district as would have been expected from historical practices. However, the features that were historically described as characteristic of Chewa life explained variation in empowerment outcomes across many of the domains included in the study. Moreover, the findings give reason to question narratives common to development that view household-headship and responsibility for farm labor as disempowering for women, rather than understanding them as potential sources of independence when they co-occur with cultural gender norms that endorse women's rights to control their own property and wealth.